The influence of Big Five personality traits on college students’ key competencies: the mediating effect of psychological capital - Hu, Anqi; Li, Xueyan; Song, Hongfeng (Frontiers in Psychology, 2023)
Background: In recent years, both society and employers have put forward higher requirements for the comprehensive quality of college students in the new era. Based on the Conservation of Resources Theory and Life-Cycle Approach, this study aimed to examine the relationship between the Big Five personality traits, the psychological capital, and the key competencies among college students and analyzed the mediating role of the psychological capital in this link.Methods: A total of 1,132 Chinese undergraduates (67.40% girls; 48.67% from key universities) participated. Participants completed self-report questionnaires that evaluated the five key characteristics of personality, psychological capital, and key competencies.Results: There were extremely significant university-type differences in key competencies of college students. And the mediating role of psychosocial capital in the link between Big Five personality traits and key competencies was validated according to PROCESS model 4. Psychological capital serves as a partial mediator in the relationships between neuroticism and critical thinking, openness and creativity, conscientiousness and creativity, openness and communication, conscientiousness and communication, extraversion and collaboration, as well as openness and collaboration. The proportion of mediating effects for the above models was 5.97%, 10.89%, 11.82%, 12.24%, 11.98%, 12.39%, and 22.72%, respectively. Discussion: The findings provide a better understanding of the key competencies of college students from the perspectives of the Big Five personality traits and psychological capital and suggest a greater emphasis to focusing on personality and improving psychological capital.